TIKTOK AS A MEDIA ECOLOGY FOR PMO PREVENTION EDUCATION: A STUDY ON THE @NOFAPS.ID ACCOUNT - Muhammad Newton Dilan Salman Haqillah; Kartikawati, Dwi (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Increasing exposure to digital content related to sexual behavior has heightened the need for education on preventing Pornography, Masturbation, and Orgasm (PMO) on platforms popular among adolescents, such as TikTok. This study aims to explain how the TikTok account @nofaps.id functions as an educational platform for PMO prevention through the lens of Media Ecology theory. A qualitative approach was employed, including in-depth interviews with the account administrator and several followers, alongside observations of PMO educational content. Findings indicate that TikTok provides a digital environment facilitating the gradual development of knowledge, awareness, and behavioral change. This occurs through short-form content, engaging visuals, and interactive features, which strengthen users’ motivation, self-control, and cognitive processes throughout PMO prevention stages. Additionally, interactions between the admin and followers via comments and consultative services create a social support space that reinforces experiential learning. The study concludes that Media Ecology theory is effective in understanding how TikTok shapes an educational ecosystem around sensitive issues such as PMO addiction. Limitations include the small number of informants and focus on a single account; future research should examine multiple platforms and adopt more diverse methodologies.